THE USABILITY OF WHATSAPP MESSENGER AS ONLINE TEACHING-LEARNING MEDIA - Darman Fauzan Dhahir (Journal of Information Technology and Its Utilization, 2020)
In order to prevent the spread of Covid-19, whether ready or not, education policy makers in Indonesia have established a policy of online learning from home. Some schools use a special Learning Management System (LMS) application, while others simply use existing common communication applications, including WhatsApp Messenger. This study aims to measure its usability in its use as an online learning medium. This research uses a descriptive quantitative approach. The data were obtained from an online survey of students and teachers who were determined by convenience sampling technique. Measurements were carried out with ISO for HCI and Usability 2001. The results showed that the Usability of WhatsApp was rated in the sufficient category, close to the good category.